Subsets of the population benefitting from the pandemic: What policies and practices should be arranged to sustainably maintain beneficiaries' mental health - Hung, Jason (Frontiers in Sociology, 2022)
Here researchers have the disposition to engage in the scholarly discourse on how the pandemic adversely influenced individuals’ mental health and what remedies should be exercised in response to the mental health challenges. There is a shortage of scholarly discussion about who benefitted from the occurrence of the pandemic. Mancini et al. argued that the pandemic benefitted the social and mental health functioning of a subset of the population, despite the pandemic causing considerable risks of harm to mental health. In this perspective, the author summarises relevant findings and arguments to present which subsets of the population benefitted at school, at home, and in the workplace during the pandemic. Although COVID-19 is no longer deemed a pandemic, many by-products of the public health crisis, including the encouragement of remote work and studies, remain. In this perspective, by understanding who benefitted from the pandemic and why, the author can evaluate if any public policies formed in response to the pandemic should be kept in the long run in order to maximise individuals’ mental health.